Thermal Comfort Condition in Affandi Museum Yogyakarta - Azka Millatina; Nedyomukti Imam Syafii (Department of Architecture and Planning, Faculty of Engineering, Universitas Gadjah Mada, 2021)
Thermal comfort is a basic human demand in interacting with space/architectural design. Determination of thermal comfort criteria can help the designer/architect in improving quality, function, and user thermal experience in an artificial environment. ISO 7730: 1994 standard states that the thermal sensation experienced by humans is the result of climate parameters (such as air temperature, radiation temperature, humidity, and wind speed) and human parameters (such as activity and clothing). These parameters were the focus of this study. The work program of this research collaboration was basically divided into 2 phases of activity, namely measuring and monitoring the conditions of thermal comfort in the Gallery 1 environment, Affandi Museum and providing recommendations for improvement of Gallery 1 thermal environment conditions. Primary data was taken from the indoor and outdoor measurement of air temperature, relative humidity and air velocity for 6 months. Physical architectural measurement of this study building and questionnaire methods followed the ASHRAE scale which was simplified to determine the level of thermal comfort, the scale of which was 2 (hot) to -2 (cold). The result of the measurement and analysis using a calculator based upon the ASHARE standard indicated that Gallery 1 of the Affandi Museum was in uncomfortable conditions. While the results of the questionnaire of 20 analyzes showed that at least 87,5% of respondents felt discomfort in Gallery 1, however, 60% of the respondent were still able to enjoy the collection and the atmosphere in gallery 1. The effective temperature index which provide 27,5-27,6 C and 66,7% RH as acceptable indoor environment in warm humid climate at Affandi museum case.